School feeding programmes and their effect on enrolment and retention in public primary schools in Tharaka-Nithi County - Muriungi, Pamella Karambu; Mbijiwe, Jane; Koech, Peter Kibet; M’Rithaa, Mugendi Kanampiu (International Journal of Education and Research, 2025)
Access to universal primary education is a key priority for many countries trying to achieve the millennium development goals. Education is a fundamental right for every person due to its contribution to equity. Kenya has not been left behind. Her Vision 2030 overall goal is to provide a global competitive quality education, reduce illiteracy, improve transition rates from primary to secondary schools and raise the quality and relevance of education. This dream can only be realized if learners from marginalized communities especially in Arid and Semi-Arid Lands accessed and got retained in schools. The purpose of this study was to investigate the effect of School Feeding Programme on enrolment and retention of learners in public primary schools in Tharaka-Nithi county in Kenya. The study adopted mixed methods approach and gathered both qualitative and quantitative data. The multi-stage study made use of varied data collection tools including questionnaires, interview schedules, focus group discussions and school records. Quantitative data was analyzed using descriptive statistics while qualitative data was organized into themes. The target population for this study was the County Director of Education, school management board members, headteachers, teachers and parents of Grade six pupils in public primary schools. The study established that school feeding program influenced the enrolment of pupils in primary school in Tharaka Nithi county. The study also established that the school feeding programme influenced the retention of pupils in schools in the county. The study established that school feeding programmes enhanced the participation of the pupils in class as their participation was described as lively. The study therefore concluded that school feeding program influenced the enrolment of pupils in primary school; the retention of pupils in schools and enhanced active participation of the pupils in class as hunger was the number one reason for dropout. The study recommended that the government should increase the coverage of the areas under school feeding programme especially the regions prone to drought with the view to improving the enrolment rates; the government should ensure there is a constant supply of school meal so as to retain the pupils in school. attend school regularly; the government and the donors should ensure the school meal has the right nutrients so as to keep the children alert in class to actively participate in the learning process.
Keywords: Enrollment; Retention; Active Participation; Tharaka- Nithi County